The Assessment Component of Employment Counselling: Some Suggestions - Patsula, Philip J.; Boyle, James E. (Canadian Journal of Counselling and Psychotherapy, 1980)
Employment counselling services may be conceptualized as assessment followed by intervention to facilitate the movement of "not-job-ready" clients towards effective employment. Reported herein is a suggested approach to be used by employment counsellors within the assessment component of the sequence.